PERKEMBANGAN PERADILAN AGAMA PASCA LAHIRNYA UU NOMOR 7 TAHUN 1989 HINGGA SAAT INI (KEWENANGAN, PEMBINAAN, PENGAWASAN DAN DASAR HUKUM) - Basri Basri (IAIN Ambon, 2017)
The existence of Law No. 7 of 1989 on Religious Courts is an implementation of Law Number 14 of 1970 on Basic Provisions of Judicial Power. Post-birth Act No. 7 of 1989 has changed through Act No. 3 of 2006. So that there is a change of power in the environment of Religious Courts. Law No. 3 of 2006 extends the authority of the Religious Courts to the handling of zakat, infaq and syari'ah economics cases. Meanwhile, the new Law on Religious Judicature, No. 50/2009 contains new changes / additions.